Pengaruh Keaktifan Siswa dalam Mengikuti Program Bina Pribadi Islam (BPI) Terhadap Kedisiplinan Beribadah di SMK Islam Inayah Kecamatan Ujungbatu Kabupaten Rokan Hulu - Jais; Risnawati; Miftahil (GHIROH, 2023)
This research aims to determine the influence of students' active participation in the Islamic Personal Development Program (BPI) on the prayer discipline of class X APHP and X TKJ students at Inayah Islamic Vocational School, Ujungbatu. This type of research is quantitative descriptive, the population used is 20 students of class X APHP and 25 students of X TKJ. The sampling technique was saturated sampling, namely 45 students. Data collection was carried out through observation and questionnaires. Data analysis techniques used were validity tests, reliability tests, normality tests, multicollinearity tests, simple regression tests, t tests and determinant tests. The results of hypothesis testing show that; Students' activeness in participating in the Islamic Personal Development Program (BPI) has a positive or significant effect on students' prayer discipline as seen in the rcount of 12,832 > 3,779 and sig. Amounting to 0.01 < 0.05.